A functional proline switch in cytochrome P450(cam) - OuYang, Bo (2008)
The two-protein complex between putidaredoxin (Pdx) and cytochrome P450(cam) (CYP101) is the catalytically competent species for camphor hydroxylation by CYP101. We detected a conformational change in CYP101 upon binding of Pdx that re-orients bound camphor appropriately for hydroxylation. Experimental evidence shows that binding of Pdx converts a single X-proline amide bond in CYP101 from trans or distorted trans to cis. Mutation of proline 89 to isoleucine yields a mixture of both bound camphor orientations, that seen in Pdx-free and that seen in Pdx-bound CYP101. A mutation in CYP101 that destabilizes the cis conformer of the Ile 88-Pro 89 amide bond results in weaker binding of Pdx. This work provides direct experimental evidence for involvement of X-proline isomerization in enzyme function.